Baitul Maal wat-Tamwil’s Financing Model to Support Micro Small and Medium Enterprises - Hamilunni'am, Moh; Fatwa, Nur (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This paper discusses Indonesian Baitul Maal wat-Tamwil product innovations. BMT is still seen as exclusive, especially for micro, small, and medium enterprises. BMT still lacks dissemination. Its products also resemble banks'. Thus, it affects public perception of banking's equality with BMT. BMT is more complicated and easier than banking. BMT is everywhere but rarely used. Thus, MSME financing needs innovation. BMT's financing products should be promoted through new innovations and increased dissemination. Thus, banking products will differ from non-bank financial products in the future. Qualitative, descriptive-analytic, data-source-adapted data collection is used in this study. Interviews and observations collected data. Literature studies provided secondary data. After revising, reducing, analyzing, and presenting the data, conclusions and research results were written. This study found that BMT's Mudharabah Empowerment Card (MEC) can solve MSMEs' non-bank financial institution financing problems.